Cervical disc disease in whippets: Results of an online survey involving Italian owners and breeders - Diletta Dell'Apa; Ezio Bianchi; Luigi Auletta; Mariaelena de Chiara; Fabiana Micieli; Francesco Ferrari; Barbara Lamagna; Maria Pia Pasolini (Research in Veterinary Science, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Resilience of pea genotypes issued from different selection methods in Algerian subhumid condition - Chems Eddine Tifest; Yves Brostaux; Camelia Lina Talbi; Mohamed Gaouas; Barbara Ferrari; Nelson Nazzicari; Luciano Pecetti; Paolo Annicchiarico; Meriem Laouar (Euphytica, 2025)

Transcriptional profiling of Fraxinus excelsior leaves during the early infection phase of ash dieback - Renata Callegari Ferrari; Victor Chano; Karuna Shrestha; Tania Dominguez-Flores; Maia Ridley; Barbara Fussi; Hannes Seidel; Oliver Gailing; Katharina B. Budde (Journal of Plant Diseases and Protection, 2025)
Ash dieback (ADB) has been causing the progressive decline of Fraxinus excelsior trees throughout Europe, urging research and forest management to develop strategies to combat ADB. A genetically heritable component in susceptibility to this fungal disease was reported in common gardens. Thus, exploring the molecular basis of ADB susceptibility will further support breeding initiatives in the future. We performed transcriptional profiling of infected and uninfected leaves from two ash genotypes with different susceptibility to Hymenoscyphus fraxineus . Leaf rachises were sampled one week following inoculation. Differential gene expression analysis was performed to compare between treatments in each genotype (individual response) or in genotypes and treatments combined (common response). Due to the heterogeneity in the response, only DEGs were discussed that passed stringent assessment. Our results revealed that UW1, the most susceptible genotype, showed a total of 515 differentially expressed genes (DEGs), some of them possibly suggesting a self-control mechanism, hindering an effective immune response and causing increased susceptibility. On the other hand, FAR3, the least susceptible genotype with 230 DEGs, seemed to induce a contained but more efficient response, hinting toward a salicylic acid-mediated process and activating pathogen-related (like) proteins as thaumatin-like, peroxidases, and chitinases. In the common response, 512 DEGs were modulated and transcripts from the phenylpropanoid pathway were commonly altered in both genotypes. Altogether, this work comprised an initial transcriptional exploration including two selected genotypes with distinct susceptibility to ADB, however, the heterogenous response indicated the need to further improve the experimental inoculation approach. Exploring gene expression patterns in ADB susceptibility holds promise to reveal early response mechanisms, and new markers related to susceptibility, as well as to contribute to developing strategies that may help contain ADB.

Spatial Variation in Upper Limits of Coral Cover on the Great Barrier Reef - Mariana Álvarez‐Noriega; Juan C. Ortiz; Daniela M. Ceccarelli; Michael J. Emslie; Katharina E. Fabricius; Michelle J. Jonker; Marji Puotinen; Barbara J. Robson; Chris M. Roelfsema; Tane H. Sinclair‐Taylor; Renata Ferrari (Global Ecology and Biogeography, 2024)
Aim Identifying the maximum coral cover that a coral community can sustain (i.e., its ‘upper limit’) is important for predicting community dynamics and improving management strategies. Here, we quantify the relationship between estimated upper limits and key environmental factors on coral reefs: hard substrate availability, temperature and water clarity. Location Great Barrier Reef (GBR), Australia (over 1400 km). Time Period 1990 to 2022. Major Taxa Studied Scleractinian corals. Methods We used 32 years of data on coral cover around reef perimeters. Each reef was divided into four wave‐exposure habitats depending on prevailing wind conditions. For each site, we determined if hard coral cover had reached a plateau or upper limit. Next, we extracted existing estimates of hard substrate availability, modelled water temperature and Secchi depth. Then, we quantified the relationship between these environmental variables and the upper limits. Results We found varying upper limits across the GBR, with a median of 33% coral cover and only 17% of the estimated upper limits exceeded 50% coral cover. Upper limits increased towards the southern reefs. Our results show that upper limits increased with increasing hard substrate availability and decreased with temperature and, to a lesser extent, with water clarity. Main Conclusions The upper limits estimated in this study are much lower than what is commonly assumed when modelling ecological dynamics, most likely resulting in predicted recovery rates being inappropriately high. Although hard substrate ultimately restricted upper limits, there are mechanisms constraining the proportion of hard substrate that is covered by hard corals. The negative relationship between temperature and upper limits cannot be explained by changes in macroalgal abundance but may be related to changes in species composition. The quantitative relationships between the upper limits of coral cover and environmental variables will provide critical information to prioritise sites for management interventions.

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Comparing Cerebellar tDCS and Cerebellar tACS in Neurodegenerative Ataxias Using Wearable Sensors: A Randomized, Double-Blind, Sham-Controlled, Triple-Crossover Trial - Ilenia Libri; Valentina Cantoni; Alberto Benussi; Jasmine Rivolta; Camilla Ferrari; Roberto Fancellu; Matthis Synofzik; Antonella Alberici; Alessandro Padovani; Barbara Borroni (The Cerebellum, 2023)
Cerebellar transcranial direct current stimulation (tDCS) represents a promising therapeutic approach for both motor and cognitive symptoms in neurodegenerative ataxias. Recently, transcranial alternating current stimulation (tACS) was also demonstrated to modulate cerebellar excitability by neuronal entrainment. To compare the effectiveness of cerebellar tDCS vs. cerebellar tACS in patients with neurodegenerative ataxia, we performed a double-blind, randomized, sham controlled, triple cross-over trial with cerebellar tDCS, cerebellar tACS or sham stimulation in twenty-six participants with neurodegenerative ataxia. Before entering the study, each participant underwent motor assessment with wearable sensors considering gait cadence (steps/minute), turn velocity (degrees/second) and turn duration (seconds), and a clinical evaluation with the scale for the Assessment and Rating of Ataxia (SARA) and the International Cooperative Ataxia Rating Scale (ICARS). After each intervention, participants underwent the same clinical assessment along with cerebellar inhibition (CBI) measurement, a marker of cerebellar activity. The gait cadence, turn velocity, SARA, and ICARS significantly improved after both tDCS and tACS, compared to sham stimulation (all p <0.010). Comparable effects were observed for CBI ( p <0.001). Overall, tDCS significantly outperformed tACS on clinical scales and CBI ( p <0.01). A significant correlation between changes of wearable sensors parameters from baseline and changes of clinical scales and CBI scores was detected. Cerebellar tDCS and cerebellar tACS are effective in ameliorating symptoms of neurodegenerative ataxias, with the former being more beneficial than the latter. Wearable sensors may serve as rater-unbiased outcome measures in future clinical trials. ClinicalTrial.gov Identifier: NCT05621200.

Specifications and validation of the ACMG/AMP criteria for clinical interpretation of sequence variants in collagen genes associated with joint hypermobility - Maria Pia Leone; Silvia Morlino; Grazia Nardella; Riccardo Pracella; Daniela Giachino; Luca Celli; Demetrio Baldo; Licia Turolla; Maria Piccione; Emanuela Salzano; Martina Busè; Patrizia Lastella; et al. (Human Genetics, 2023)

Genome-wide association study reveals white lupin candidate gene involved in anthracnose resistance - Joris A. Alkemade; Nelson Nazzicari; Monika M. Messmer; Paolo Annicchiarico; Barbara Ferrari; Ralf T. Voegele; Maria R. Finckh; Christine Arncken; Pierre Hohmann (Theoretical and Applied Genetics, 2022)
Key message GWAS identifies candidate gene controlling resistance to anthracnose disease in white lupin. Abstract White lupin ( Lupinus albus L.) is a promising grain legume to meet the growing demand for plant-based protein. Its cultivation, however, is severely threatened by anthracnose disease caused by the fungal pathogen Colletotrichum lupini . To dissect the genetic architecture for anthracnose resistance, genotyping by sequencing was performed on white lupin accessions collected from the center of domestication and traditional cultivation regions. GBS resulted in 4611 high-quality single-nucleotide polymorphisms (SNPs) for 181 accessions, which were combined with resistance data observed under controlled conditions to perform a genome-wide association study (GWAS). Obtained disease phenotypes were shown to highly correlate with overall three-year disease assessments under Swiss field conditions ( r > 0.8). GWAS results identified two significant SNPs associated with anthracnose resistance on gene Lalb_Chr05_g0216161 encoding a RING zinc-finger E3 ubiquitin ligase which is potentially involved in plant immunity. Population analysis showed a remarkably fast linkage disequilibrium decay, weak population structure and grouping of commercial varieties with landraces, corresponding to the slow domestication history and scarcity of modern breeding efforts in white lupin. Together with 15 highly resistant accessions identified in the resistance assay, our findings show promise for further crop improvement. This study provides the basis for marker-assisted selection, genomic prediction and studies aimed at understanding anthracnose resistance mechanisms in white lupin and contributes to improving breeding programs worldwide.

A new standardized immunofluorescence method for potency quantification (SMPQ) of human conjunctival cell cultures - Marina Bertolin; Claudia Breda; Stefano Ferrari; Mattia Lamon; Diego Ponzin; Barbara Ferrari; Vanessa Barbaro (Cell and Tissue Banking, 2021)

Conservation and enhancement of the green infrastructure as a nature-based solution for Rome’s sustainable development - Barbara Ferrari; Valerio Quatrini; Anna Barbati; Piermaria Corona; Emanuela Masini; Dalila Russo (Urban Ecosystems, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Towards xeno-free cultures of human limbal stem cells for ocular surface reconstruction - Zala Lužnik; Claudia Breda; Vanessa Barbaro; Stefano Ferrari; Angelo Migliorati; Enzo Di Iorio; Barbara Ferrari; Carlo Griffoni; Andrea Grassetto; Hossein Mostafa Elbadawy; Marina Bertolin (Cell and Tissue Banking, 2017)

Erratum to: Population genetics of pike, genus Esox (Actinopterygii, Esocidae), in Northern Italy: evidence for mosaic distribution of native, exotic and introgressed populations - Andrea Gandolfi; Claudio Ferrari; Barbara Crestanello; Matteo Girardi; Livia Lucentini; Andreas Meraner (Hydrobiologia, 2017)

Taking the pulse of forest plantations success in peri-urban environments through continuous inventory - Barbara Ferrari; Piermaria Corona; Leone Davide Mancini; Riccardo Salvati; Anna Barbati (New Forests, 2017)

Population genetics of pike, genus Esox (Actinopterygii, Esocidae), in Northern Italy: evidence for mosaic distribution of native, exotic and introgressed populations - Andrea Gandolfi; Claudio Ferrari; Barbara Crestanello; Matteo Girardi; Livia Lucentini; Andreas Meraner (Hydrobiologia, 2017)

Conversion of Mountain Beech Coppices into High Forest: An Example for Ecological Intensification - Walter Mattioli; Barbara Ferrari; Diego Giuliarelli; Leone Davide Mancini; Luigi Portoghesi; Piermaria Corona (Environmental Management, 2015)

Automated assessment of macroseismic intensity from written sources using the fuzzy sets - Gianfranco Vannucci; Daniele Tripone; Paolo Gasperini; Graziano Ferrari; Barbara Lolli (Bulletin of Earthquake Engineering, 2015)

Toxicity and persistence of three pyrethroids for the control of cereal bugs on common wheat - Marco G. Pansa; Massimo Blandino; Barbara L. Ingegno; Ester Ferrari; Amedeo Reyneri; Luciana Tavella (Journal of Pest Science, 2015)

Mutational scanning of the ABCR gene with double-gradient denaturing-gradient gel electrophoresis (DG-DGGE) in Italian Stargardt disease patients - Antonella Fumagalli; Maurizio Ferrari; Nadia Soriani; Alessandra Gessi; Barbara Foglieni; Elisabetta Martina; Maria Manitto; Rosario Brancato; Michael Dean; Rando Allikmets; Laura Cremonesi (Human Genetics, 2001)